Optimizing QTL introgression via stochastic simulations: an example of the IRRI rice breeding program - Platten, John Damien; Fritsche-Neto, Roberto (Research Square Platform LLC, 2022)
A key limitation in the ability of breeding programs to leverage benefits of major-gene marker-assisted selection is the availability of those genes in appropriate elite germplasm. In this context, our study compared three strategies to develop new recipients for QTL introgression (Background recovery (BG), Selective sweep (SS), and Breeding values (BV)) in a short-term breeding program (over five breeding cycles). Furthermore, we evaluated two different numbers of recipients (10 and 20) in the introgression process and how they influence